Аристотель о высыхании Арголиды (Meteor. I, 14, 352 a 9–13) - Верлинский, Александр Леонардович (Philologia Classica, 2007)
According to Aristotle (Meteor. I.14.352 a 9–18), Mycenae was thriving in the time of the Trojan war, while Argos was then marshy; afterwards, in Aristotle’s time, Mycenae became over-dry and fruitless, and Argos, due to the same drying up, became cultivated. Argolis is for Aristotle an example of gradual retardation of the sea due to silting activities of rivers and of gradual colonization of drying land (Argos in comparison with Mycenae is closer to the sea), the process most impressively exemplified by Egypt. The retardation of the sea in Argolis is the real fact which was ascertained in 19th century, but which was not noticed by classical writers except Aristotle. Aristotle might have used the local mythological tradition on flooding of Argolis by the sea due to rage of Poseidon or the real facts underlying it (the rests of marshes on the plain of Argos taken wrongly as the traces of the sea flood, presumably also findings of mussels on the plain) and interpreted them as pointing to retardation of the sea, not to the catastrophic flooding. This generally right explanation was probably based on knowledge of intensive silting activities of Argivean rivers, which are very poor with water as compared with Nil, but leave easily observable silt on the plain during their regularly occurring floods. Aristotle’s statement concerning situation in the heroic age is thus the inference only from his general theory of the process of drying up of Argolis, both velocity and range of which he overstated, as it was typical also for 19th century scholars.